RANCANG BANGUN ALAT PENCATAT AKTIFITAS JANTUNG MENGGUNAKAN ARDUINO UNO BERBASIS ANDROID - Khairil Abdillah; Fitria Priyulida; Abed Nego Mendrofa (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2020)
The electrical activity of the heart is the basis elektrokardiograph (ECG) in observing the condition of the heart , a series of ECG consists of amplifier biopotensial of an instrument ECG became the main component in this study , records heart activity is still a burden to the medical world in the use and the results of the expected output .In this study biolistrik signal received from the ECG to be controlled via arduino , and data received through arduino will be sent via Bluetooth and android will be shown on the display , Bluetooth serves as the sender and the data receiver ( RX,TX). Results released by android is a graphic display that can be stored in the form of images in JPEG format on a regular basis or in real time so as to facilitate and reduce the use of paper in printing graphics imaginable on ECG in general that still use paper as the output.